2018
DOI: 10.1002/cam4.1619
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of combination therapy of interferon‐α2 and ruxolitinib in polycythemia vera and myelofibrosis

Abstract: Interferon‐α2 reduces elevated blood cell counts and splenomegaly in patients with myeloproliferative neoplasms (MPN) and may restore polyclonal hematopoiesis. Its use is limited by inflammation‐mediated toxicity, leading to treatment discontinuation in 10‐30% of patients. Ruxolitinib, a potent anti‐inflammatory agent, has demonstrated benefit in myelofibrosis (MF) and polycythemia vera (PV) patients. Combination therapy (CT) with these two agents may be more efficacious than monotherapy with either, potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…However, IFN-α also represses the expression of cytokines and receptors that do not signal via JAK/STAT, notably IL-1β, a major pro-inflammatory cytokine, as well as others that facilitate the survival of MPN progenitors, such as IL-11, hepatocyte growth factor (HGF) and its receptor, c-MET, and tumor growth factors β (TGF-β) [ 24 , 25 ]. Consistently, IFN-α and JAK inhibitors were reported to act in synergy in MPNs [ 26 , 27 , 28 ]. Hence, both chronic inflammation and the JAK2 / CALR / MPL mutants play major roles in the pathogenesis of MPNs, and inflammation cytokines act as stimulants of the mutated clone as well as mediators of clinical symptoms and complications [ 12 , 29 ].…”
Section: Introductionmentioning
confidence: 77%
“…However, IFN-α also represses the expression of cytokines and receptors that do not signal via JAK/STAT, notably IL-1β, a major pro-inflammatory cytokine, as well as others that facilitate the survival of MPN progenitors, such as IL-11, hepatocyte growth factor (HGF) and its receptor, c-MET, and tumor growth factors β (TGF-β) [ 24 , 25 ]. Consistently, IFN-α and JAK inhibitors were reported to act in synergy in MPNs [ 26 , 27 , 28 ]. Hence, both chronic inflammation and the JAK2 / CALR / MPL mutants play major roles in the pathogenesis of MPNs, and inflammation cytokines act as stimulants of the mutated clone as well as mediators of clinical symptoms and complications [ 12 , 29 ].…”
Section: Introductionmentioning
confidence: 77%
“…We studied three populations: (a) 42 patients with PV or MF included in the phase II COMBI trial investigating safety and efficacy of combination therapy with RUX and IFN‐α2 (EudraCT: 2013‐003295‐12) with measurements before and during therapy; (b) 29 MF patients with measurements before and during RUX therapy; and (c) reevaluation of the flow cytometry data on lymphocyte count and B‐cell frequency in 36 patients with MPNs, mainly ET or PV, included in a previous study on NK cells and 10 HDs. Of these 36 patients, 21 were treated with IFN‐α2 with measurements before and during treatment, and 15 patients were not receiving cytoreductive treatment .…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that this potential antagonism is avoided in vivo because of the relative sparing of LT-HSC from ruxolitinib-mediated JAK/STAT inhibition [172]. Initial combination phase 2 studies showed a complete haematological response was achieved in 44% of PV patients and 58% of low to intermediate-1 risk MF at 12 months of treatment, with both groups showing a significant reduction in JAK2 V617F allele burden with a median decrease in VAF from 47% to 23.5% for PV at 12 months and 45% to 18% for MF at 12 months [202].…”
Section: Pegylated Interferon Alpha (Ifnα)mentioning
confidence: 99%